Penanaman Nilai-nilai Moderasi Beragama dalam Pembelajaran PAI di SMP Negeri 22 Padang - Ajat Hidayat; Rini Rahman (Pendidikan Agama Islam STIT Palapa Nusantara, 2022)
This study aims to find out what values ​​are contained in PAI learning in class IX at SMP Negeri 22 Padang. The method used in this research is a combination method or mixed methods. With exploratory mixed methods, the designs approach namely sequential designs starting from qualitative data collection in the first stage through in-depth interviews with two informants selected through purposive sampling technique and followed by quantitative data collection in the second stage using a questionnaire to 30 students in class IX. All data in the second stage were analyzed descriptively using the IBM SPSS Statistics 24 application. Overall, the results of this study indicate that there are four values ​​of religious moderation in PAI learning, namely in preliminary activities, core activities, and learning evaluation. The four values ​​are i`tidal, tasamuh, shura, and qudwah. The results of this study also prove that learning Islamic religious education in schools is effective in instilling the values ​​of religious moderation in students in junior high school.